Coping Flexibility and Alcohol-Related Outcomes: Examining Coping Motives as Mediators. (6th December 2022) - Jenzer, Tiffany; Cheesman, Abigail J.; Shaw, Rachael J.; Egerton, Gregory A.; Read, Jennifer P.
Abstract: Background: Coping has been implicated in the etiology and treatment of problem drinking. Traditional, static measurement of coping styles (e.g., approach, avoidance, social support) may fail to capture how adaptive a given coping style may be. Coping flexibility is an emerging construct, associated with psychological health, and one that may shed light on coping's role in drinking risk. Coping flexibility includes (1) discontinuation of an ineffective coping strategy (" Discontinuation ") and (2) production of an alternative strategy (" Implementation "). This study is the first to our knowledge to examine its association to drinking outcomes. Further, because coping deficits are theorized to lead to drinking through coping motives, we also examined mediated pathways from coping flexibility to alcohol outcomes via coping motives. Methods: College students ( N  = 528) completed an online assessment. Data were analyzed using path analysis. Control variables included sex and coping styles. Results: In path analytic models, Implementation was negatively associated with alcohol use and, indirectly via coping motives, negatively associated with alcohol consequences. The direct effect on alcohol use remained when controlling for coping styles and sex, but the mediational pathway was no longer significant. Conclusions: This study provides some evidence for the protective role of coping flexibility in alcohol use behavior, which may have implications for how best to address coping skills in alcohol interventions. The direct effect of Implementation on drinking suggests that there may be utility in teaching clients a flexible approach to coping in treatment. Replication, particularly with longitudinal designs, is needed.